Clinical competency of nurses trained in competency-based versus objective-based education in the Democratic Republic of the Congo: a qualitative study - Mari Nagai; Miyuki Oikawa; Tomoko Komagata; Josué Désiré Bapitani Basuana; Gérard Kahombo Ulyabo; Yui Minagawa; Sadatoshi Matsuoka; Yuriko Egami; Mari Honda; Toyomitsu Tamura (BMC, 2024)
Abstract Background Designing competency-based education (CBE) programmes is a priority in global nursing education for better nursing care for the population. In the Democratic Republic of the Congo (DRC), object-based education (OBE) remains mainstream in pre-service nursing education programmes. Recently, the Ministry of Health developed a self-assessment tool and quantitatively compared the clinical competency of CBE- and OBE-trained nurses. This study aimed to qualitatively triangulate the results of self-evaluation by exploring perception of supervisors, incumbent CBE-, and OBE-trained nurses in comparison with the competence of the two types of nurses, and to identify influential factors or barriers to their competence in clinical settings. Methods A qualitative descriptive approach with conventional content analysis was applied. Twenty interviews with clinical supervisors who oversaw both CBE- and OBE-trained nurses, 22 focus group discussions (FGDs) with CBE-trained nurses, and 21 FGDs with OBA-trained nurses currently working in health facilities were conducted. Participants of the FGDs were selected from the participants of the DRC self-assessment competency comparison study where there was no statistically significance between CBE- and OBE-trained nurses in the demographic characteristics. Data were analysed in terms of the competencies identified by the Ministry of Health. Results The supervisors recognised that the CBE-trained nurses had stronger competencies in professional communication, making decisions about health problems, and engaging in professional development, but were weak in clinical skills. This study identified challenges for supervisors in assuring standardised care in health facilities with OBE- and CBE-trained nurses, as well as barriers for CBE-trained nurses as a minority in the workplace in demonstrating their competencies. Conclusions The study results support the Ministry of Health's policy to expand CBE in pre-service education programmes but reveal that its slow implementation impedes full utilisation of the acquired competencies at health facilities. Implementation could be accelerated by strengthening cooperation among the Ministry of Health's three human resource departments, and developing and implementing a well-planned, legally binding, long-term CBE reform strategy, including an approach to the Continuing Professional Development system.